Evaluation of Language Programs in Course Institutions to Improve Student Learning in Facing the IELTS Exam - Firdaus, Saiyidinal; Ramadhan, Saiyidinal Futhra; Suseno, Muchlas; Setiadi, Samsi (STBA Prayoga Padang, 2025)
This study aims to evaluate the effectiveness of the English language program at the Time Language Center Padang Course Institute to improve students' learning abilities in facing the IELTS exam. The evaluation was conducted using a summative evaluation model that focuses on assessing learning outcomes after the program is completed. The data used in this study were questionnaire data filled out by students regarding their learning experiences and perceptions of increased abilities, as well as field observation data covering teaching methods, classroom interactions, and learning environments. The analysis method includes questionnaire validity and reliability tests to ensure data accuracy, as well as weighting methods to assess important aspects of the program. The evaluation results show that the language program at Time Language Center makes a significant contribution to improving students' readiness to face the IELTS exam, especially in the aspects of listening and reading comprehension. However, there are several weaknesses in the speaking skills aspect that need to be improved and evaluated. Recommendations proposed include improving interactive teaching methods and adding intensive speaking practice sessions. This study provides a comprehensive overview of the effectiveness of language programs and the importance of summative evaluation as a measuring tool for learning success in the context of exam preparation such as IELTS, so that it can be a reference for other course institutions in developing more effective and measurable learning programs.